Pengaruh Reputasi, Hasil, Persyaratan, Perilaku Etis, Dan Niat Kerja Terhadap Persepsi Mahasiswa Akuntansi Di Semarang Mengenai Karir Akuntansi Berdasarkan Gender - Stefanus Jusvian; Stephana Dyah Ayu Retnaningsih (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Commonly, perceptions between men and women can be different. Men and women can sometimes view a career with their own perceptions according to the information they get. Students majoring in accounting in Semarang are the population of this study. This study used a random sampling method with the distribution of questionnaires. This study used 273 respondents of active students majoring in accounting in Semarang. Hypothesis testing is performed using the t-test. This study aims to see the perception of accounting students regarding the accountant profession based on gender. This study shows that the variables of work requirements, work reputation, intentions (feelings), and work outcomes have no difference in perception based on gender. Meanwhile, the variable negative perception of accounting work gives significant results between men and women. Keywords: Accountant Career, Gender, Student Perception, Accountant Profession